STUDY OF VOLTAGE CHARACTERISTICS OF THE SOLAR ELEMENT nCdS / pCdT? WITH A THIN TRANSITION i-LAYER DEPENDING ON TEMPERATURE (Archive of Conferences, 2020)
In this work, the current-voltage characteristics of a thin-film CdS / CdTe solar cell with a transition i-layer of the interface from a solid solution CdTe1-xSx were investigated depending on the temperature. trap density, metal function, temperature, which can affect the efficiency of a CdS / CdTe solar cell.